2022
DOI: 10.1021/acsearthspacechem.2c00098
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Clays for Radionuclide Sequestration: A Review

Abstract: Performance assessment of nuclear waste disposal options requires implementation of effective buffer materials. Buffer materials must meet longevity requirements and scavenge challenging radioisotopes, e.g., iodine-129 (I-129) and technetium-99 (Tc-99), both long-lived, highly mobile, anionic species in oxic environments. In many proposed nuclear waste repositories, heat generating radioactive waste will be surrounded by clay buffer material, which swells to fill the gap between the waste package and the host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 232 publications
0
4
0
Order By: Relevance
“…Compared with quaternary ammonium salts of the same molecular structure, quaternary phosphonium salts are easier to synthesize, have higher heat resistance, lower liquid crystal state onset temperature and wider liquid crystal phase temperature interval 16–18 . They are more and more popular among researchers because their thermal degradation temperature is above 300°C and they do not thermally degrade when used to modify polymer materials, which is more conducive to improving the thermal stability of materials 19–22 . However, foreign reports on their specific synthesis methods are incomplete, 23 and domestic research is also immature, so the synthesis methods need to be explored in terms of reaction conditions and reaction solvents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with quaternary ammonium salts of the same molecular structure, quaternary phosphonium salts are easier to synthesize, have higher heat resistance, lower liquid crystal state onset temperature and wider liquid crystal phase temperature interval 16–18 . They are more and more popular among researchers because their thermal degradation temperature is above 300°C and they do not thermally degrade when used to modify polymer materials, which is more conducive to improving the thermal stability of materials 19–22 . However, foreign reports on their specific synthesis methods are incomplete, 23 and domestic research is also immature, so the synthesis methods need to be explored in terms of reaction conditions and reaction solvents.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] They are more and more popular among researchers because their thermal degradation temperature is above 300 C and they do not thermally degrade when used to modify polymer materials, which is more conducive to improving the thermal stability of materials. [19][20][21][22] However, foreign reports on their specific synthesis methods are incomplete, 23 and domestic research is also immature, so the synthesis methods need to be explored in terms of reaction conditions and reaction solvents.…”
mentioning
confidence: 99%
“…The build-up concentration of carbonate ions in the solution caused by its relatively high steric hinderance (bulkiness) increases the iodide ions flux towards the active sites of the MOF, thereby increasing the iodine update in the presence of CO 3 2– . The electronegativities of the elements that are contained in the three anion groups are listed in ascending order C ∼ I ≪ Cl < O. Combining the aforementioned effects of CO 3 2– and Cl – on the uptake of I – , a solution of these three anions was prepared and their combined effects were studied accordingly. Figure revealed that the adsorption of I – in the Cl – and CO 3 2– containing solution was much more effective compared to a solution containing only iodide ion.…”
Section: Resultsmentioning
confidence: 99%
“…40,41,43 On the one hand, there should be the presence of substances with an amorphous structure 43 and/or the formation of a disordered pillared structure, 7 which was confirmed by SEM characterization (discussed below, Figure 5a,f), and was consistent with the basal spacing. On the other hand, the inner-sphere complexation may occur between fully or partially dehydrated Cs and the more durable siloxane groups where Cs irreversibly bound between the upper and lower tetrahedral sheets, resulting in collapsing interlayers 6,44,45 It was also shown in AFM (Figure 6f) that the distinct columnar, as well as the uniform, rounded, and thick structures appeared. Benedicto et al 46 also found that the interlayer of illite collapsed after it adsorbed the Cs ion.…”
Section: Characterization Of Adsorbents and Sr/csmentioning
confidence: 99%